ELECTRICAL AND SHIELDING PROPERTIES OF ACRYLONITRILE BUTADIENE STYRENE FILLED WITH DIFFERENTLY TREATED RECYCLED CARBON FIBERS - Alkaseh, A.M.; Manaf, M.E.A.; Mohamad, N. (Journal of Advanced Manufacturing Technology (JAMT), 2022)
Polymeric composites have been studied for electromagnetic interference (EMI) shielding material due to their many advantages including low density, good flexural and impact strength, and ease of processing. Recycled carbon fiber has the potential as conductive filler in polymer composites, however the effects of different treatment such as irradiation on the properties is still lacking. A comparative study based on different fiber treatments and electron beam irradiation on recycled carbon fibers (rCF) filled acrylonitrile butadiene styrene (ABS) composites has been carried out and the results are presented in this paper. The main objective is to evaluate how these treatments impact properties such as conductivity and shielding effectiveness (SE) of the composites. Three types of filler, i.e., untreated rCF, chemically treated rCF, and chemically-mechanically treated rCF are used as to improve the electrical conductivity of ABS polymer. In order to enhance shielding effectiveness of the composites, electron beam (EB) irradiation is applied at 200 kGy to induce cross linked networks. The composite samples are prepared by using melt compounding method. In general, composites reinforced with treated rCF show better performance in both conductivity and shielding effectiveness. Moreover, for the same fiber amount, the electrical conductivity of the composites filled with irradiated-recycled carbon fibers is much higher than that of non-irradiated recycled carbon-fiber-filled composites. By using irradiated-recycled carbon fibers as filler, in order to achieve the same degree of conductivity as carbon fiber filled composites, the required volume fraction of fibers can be greatly reduced. From the results, the EB irradiated composite with 30 wt% chemically treated rCF shows the best shielding effectiveness and electrical conductivity, where the highest values reached are 1.34 × 10-8 S/m and 46.13 dB, for electrical conductivity and shielding effectiveness, respectively. This finding is significant as to better understand the behavior of rCF filled ABS composites especially for EMI shielding application.